Study of the Energy Characteristics of Metallized Mixed Compositions Based on a Binary Oxidizer at Increased Pressures; Russian Physics Journal; Vol. 57, iss. 5 - Gorbenko T. I. Tatiana Ivanovna; Gorbenko M. V. Mikhail Vladimirovich; Dyundin E. O. Evgeny Olegovich; Zolotorev N. N. Nikolay Nikolaevich (2014, 2014)
Title screen